Analisis Deskriptif Kualitas Pelayanan Terhadap Tingkat Kepuasan Masyarakat pada Kantor Desa Orahili Tanose'o Kecamatan Gunungsitoli Alo’oa (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to analyze the quality of service in relation to community satisfaction at the Orahili Tanoseo Village Office, Gunungsitoli Alooa Sub-district. The focus of this research includes three main objectives: to determine the quality of public services provided by the village officials, to understand the level of community satisfaction with the services received, and to identify the resource limitations that affect service quality at the village office. This study employed a qualitative method with data collection techniques through observation, interviews, and documentation. The research findings indicate that, in general, the quality of service provided by the Orahili Tanoseo Village officials has attempted to meet the community’s needs. However, there are still some shortcomings, such as slow service and a lack of friendliness from the service providers. The level of community satisfaction tends to vary; some community members are satisfied with the services provided, while others still complain about slow processes and insufficient information. Additionally, resource limitations, including the number of staff, infrastructure, and technological support, remain challenges that hinder the optimal delivery of public services at the Orahili Tanoseo Village Office. Therefore, efforts to improve service quality and system efficiency are needed to better meet the expectations of the community.